Membangun Literasi Ekonomi Digital Siswa Melalui Pembelajaran Mendalam Berbasis Proyek - Yuni Rahayu, Purwati; Eliyani , Citra; Widya Lestari , Ambar (Universitas Pamulang, 2026)
This Community Service (PKM) activity aims to improve students' digital economic literacy through the application of a project-based deep learning approach (PjBL). The activity implementation method includes planning, implementation, reflection, and follow-up stages. The activity was held at Nurul Falaah Senior High School, Gunung Sindur, Bogor Regency, for three days, October 16–18, 2025, with 30 students participating. The activity was carried out through workshops, interactive presentations using digital media, and reflective discussions. The results of the activities showed an increase in students' understanding of the concept of digital economic literacy and their ability to connect economic theory with digital economic phenomena in everyday environments. Students were able to demonstrate a more critical and wise attitude in making technology-based economic decisions, as well as understanding the risks and opportunities that arise in digital economic activities. Teachers also gained new insights into the application of project-based learning and in-depth learning strategies that are contextual and applicable. Keywords: Digital Economic Literacy, Immersive Learning, Project-Based Learning, Economic Education, 21st Century.